Pendampingan Masyarakat Desa dalam Meningkatkan Moderasi Beragama Dan Memupuk Kepedulian - Wajdi, Muh Barid Nizarudin (STAI Miftahul ULa Nganjuk, 2023)
This assistance aims to enhance religious moderation and foster compassion through the Participatory Action Research (PAR) method in Sidoharjo Village, Oro-Oro Ombo Hamlet, Tanjunganom Subdistrict, Nganjuk Regency. The results of the assistance indicate that through community assistance based on PAR, there is an improvement in understanding of religious moderation and the instillation of values of compassion among residents. This process involves various activities such as training, interactive dialogues, and other participatory activities. These results reflect positive changes in attitudes, knowledge, and behaviors of the community regarding religious moderation and social compassion. In conclusion, community assistance with the PAR method can be an effective instrument in building religious moderation and compassion at the local level. It is expected that the findings of this research can contribute to the development of a community assistance model that can be adopted in various contexts to enhance the quality of religious and social life in the community.